Analisis Kendala dan Solusi dalam Penerapan Literasi terhadap Minat Baca Siswa Kelas V di SDN 90/II Talang Pantai Kabupaten Bungo - Edi Sulistiono; Apdoludin Apdoludin; Randi Eka Putra (CV. Master Literasi Indonesia, 2025)
This study was conducted based on the phenomenon of low reading interest among elementary school students, even though literacy programs have been routinely implemented in schools. This condition indicates that literacy activities have not yet been fully effective in fostering sustainable reading habits among students. The purpose of this research is to identify the obstacles faced in the implementation of literacy programs, analyze the role of teachers in supporting literacy activities, and formulate appropriate solutions to improve the reading interest of fifth-grade students at SDN 90/II Talang Pantai, Bungo Regency. This study employed a qualitative descriptive approach. The research subjects consisted of 31 fifth-grade students, a classroom teacher, and the school principal. The object of the study focused on the implementation of literacy activities in the classroom. Data collection techniques included observation, semi-structured interviews, and documentation. The instruments used were observation sheets and interview guidelines based on reading interest indicators. Data analysis was carried out through data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation of sources, techniques, and time.The findings reveal that the main obstacles in literacy implementation include limited availability of reading materials that align with students’ interests, low reading habits at home, lack of confidence among students in reading activities, and limited variation in teaching methods. The solutions identified include providing more diverse and engaging reading materials, integrating literacy activities into daily learning processes, giving motivation and rewards, and strengthening collaboration between schools and parents. The study concludes that literacy programs can significantly enhance students’ reading interest when implemented consistently, creatively, and collaboratively